1982
DOI: 10.1159/000179496
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygotes and Cryptic Patients in Families of Patients with Congenital Adrenal Hyperplasia (21-Hydroxylase Deficiency)

Abstract: In a group of 18 unrelated Danish children with 21 -hydroxylase deficiency (21 -OH def), human leukocyte antigen (HLA) typing revealed a significant increase of Bw47 and a significant decrease of B8. HLA studies of the families of 14 probands predicted among the siblings 11 heterozygote carriers and 3 genetically unaffected. Glyoxalase studies showed a recombination fraction of 8%. ACTH-stimulated 17-OH progesterone is the only hormone value useful in the discrimination between heterozygotes and normals. Two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…The results of the hor¬ monal studies of our patients with 'non-classical' 21-OH deficiency are in agreement with the results of other investigators (Levine et al , 1981Petersen et al 1982). Therefore, our hormonal studies combined with HLA typing were not able to differentiate if the father's genotype a/b and the daughter's geno¬ type a/c represent a combination of a gene for the severe with a gene for the mild form of the disease (21-OHsevere/21-OHmild), or a combination of two genes for the mild form of 21-OH deficiency (21-OHmild/21-OHmild).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the hor¬ monal studies of our patients with 'non-classical' 21-OH deficiency are in agreement with the results of other investigators (Levine et al , 1981Petersen et al 1982). Therefore, our hormonal studies combined with HLA typing were not able to differentiate if the father's genotype a/b and the daughter's geno¬ type a/c represent a combination of a gene for the severe with a gene for the mild form of the disease (21-OHsevere/21-OHmild), or a combination of two genes for the mild form of 21-OH deficiency (21-OHmild/21-OHmild).…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm the hypothesis that the in¬ dividuals with the 'non-classical', 'cryptic' form of 21-OH deficiency are genetic compounds, bearing one alíele for the severe, classical form and on the homologous locus, another alíele for the mild, 'non-classical' form of 21-OH deficiency (21-OH^vere/2l-OHmüd) (Levine et al , 1981Petersen et al 1982). Like the alíele for the severe, classical form which is genetically linked to the HLA-system (New et al 1983), there is strong evidence from other studies that the alíele for the mild, 'non-classical' form of 21-OH deficiency is as well linked to the HLA system, being in genetic disequilibrium with the 14 and DR 1 antigens (Laron et al 1980;Pollack et al 1981;Coullin et al 1982;O'Neil et al 1982).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Several studies from various groups have conveyed that between 50 and 80% of carriers exhibit a 17-OHP level after ACTH stimulation and that is above the 95th percentile of the control value [37, 39, 42, 45]. The purpose of this study was to determine the frequency of identified defects of the CYP21A2 gene and also to weigh the regulatory 3′UTR region of the gene in a clinically symptomatic cohort of 169 females, characterized by hyperandrogenaemia.…”
Section: Introductionmentioning
confidence: 99%